Implementasi Strategi Pembelajaran Berbasis Proyek dalam Pembelajaran Pendidikan Agama Islam dan Budi Pekerti di SDN Bhakti Winaya 223 Kota Bandung - Fitria, Ayu; Aldi, Maulana; Sopiah, Neng Siti; Widjaya, Cheppy Risnandar Angga (Tarbiatuna: Journal of Islamic Education Studies, 2025)
Islamic Religious Education (PAI) and Character Building in Elementary Schools play a central role in instilling religious values and shaping students character from an early age. Project-Based Learning (PjBL) is an innovative learning strategy that encourages students to be active, creative, and contextual in understanding religious material. This study aims to examine the implementation of project-based PAI learning in elementary schools and analyze its impact on students understanding of Islamic values and the development of social attitudes. The study used a qualitative approach with descriptive analysis methods. Data collection techniques included observation, interviews, and documentation studies. The results indicate that project-based learning strategies in Islamic Religious Education and Character Building can increase student participation, develop religious attitudes, and strengthen social skills. However, several obstacles remain, such as time constraints, lack of teacher training, suboptimal school support, and the lack of development of student critical thinking skills.